Fast neutrons detection in CR-39 and DAM–ADC nuclear track detectors. (March 2015) - Abdalla, A.M.; Ashraf, O.; Rammah, Y.S.; Ashry, A.H.; Eisa, M.; Tsuruta, T.
Abstract: Fast detection of neutrons in CR-39 and DAM–ADC nuclear track detectors were investigated using new etching conditions. The neutron irradiation is performed using a 5 mCi Am–Be source present at the National Institute of Standards (NIS) of Egypt. Using the new etching condition, irradiated CR-39 samples were etched for 4 h and DAM-ADC samples for 80 min. Suitable analyzing software has been used to analyze experimental data.The dependence of neutrons track density on the neutrons fluence is investigated. When etched under optimum conditions, the relationship between track density and fluence is determined which is found to be linear. Detection efficiency has been represented for both SSNTDs and found to be constant with fluence, which reflects the importance of using CR-39 and DAM–ADC detectors in the field of neutron dosimetry. Linear relationship between track density and effective dose is determined. Highlights: Fast neutron detection in CR-39 track detector. Relationship between effective doses as a function of the track density. Detection efficiency of CR-39 and DAM–ADC for fast neutrons.